Rehabilitation in Patients Diagnosed with Arthrogryposis Multiplex Congenita: A Systematic Review - Catalina E. García Aguilar; Cristina García-Muñoz; Ines Carmona-Barrientos; Maria Jesus Vinolo-Gil; Francisco Javier Martin-Vega; Gloria Gonzalez-Medina (MDPI AG, 2023)
Arthrogryposis multiplex congenita is a condition characterised by contractures and deformity in two or more body areas. Physiotherapy may be an appropriate treatment. The aim was to systematically review the evidence for rehabilitation in arthrogryposis multiplex congenita. A systematic review was performed following the PRISMA 2020 criteria. The search was conducted in PubMed, ScienceDirect, Scielo, Scopus, Web of Science, ENFISPO, JSTOR, Google Scholar, ProQuest, Cochrane Library and PEDro from inception until October 2022. To assess the methodological quality, we used the different aspects of the critical appraisal tool JBI. We included 14 studies (6 case reports, 5 case series, 2 cross-sectional and 1 qualitative study). Sample sizes ranged from 1 to 50 participants, with an age range between 11 days and 35 years. Most studies employed multicomponent therapy, mainly kinesitherapy, massage therapy, use of physical agents and stretching, some combined it with orthopaedic therapy, or it was complementary to surgical treatment. The key to improving the clinical picture was early and individualised care, tailored to the characteristics of the patients. Regarding methodological quality, the main conflicts encountered were in the reporting of participant characteristics and experimental interventions. Rehabilitation provides satisfactory results in the treatment of arthrogryposis multiplex congenita. More scientific production and randomised clinical trials are needed.